Self-Efficacy sebagai Prediktor Intensi Kewirausahaan Digital Mahasiswa Akuntansi - Hikmayani Subur; Sri Utami (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the influence of self-efficacy on digital entrepreneurial intention among accounting students. The study focuses on students' beliefs in their ability to start a business, make decisions, use business technology, solve problems, and deal with risks in a digital business context. A quantitative explanatory design was employed involving 150 accounting students at the Faculty of Economics and Business, Universitas Negeri Makassar, selected using purposive sampling. Data were collected through a closed-ended questionnaire using a five-point Likert scale and analyzed with Structural Equation Modeling-Partial Least Squares. The findings show that self-efficacy has a positive and significant effect on students' digital entrepreneurial intention, with a path coefficient of 0.288, a t-statistic of 3.951, and a p-value of 0.000. The effect size of 0.094 indicates that the unique contribution of self-efficacy is small, yet empirically meaningful in explaining students' psychological readiness to enter the digital entrepreneurship ecosystem. These findings imply that strengthening digital entrepreneurial intention should not rely solely on technological mastery, but should also involve experiential learning that enhances students' confidence in managing digital business activities.